Comparative study of sexual concentration in the elimination of sexual violence from feminist and Islamic legal theory - Sutisna,; Hambari,; Ratih, (Technium Education and Humanities, 2023)
Feminist legal theory (FLT) is a critical legal movement in Indonesia. FLT takes issue with laws that prioritize masculine values, which limit social values because the law is dominant towards men and oppresses women. The paradigm of sexual consent was incorporated into Indonesian law as a result of this FLT movement. The focus of this research is how sexual consent affects the elimination of sexual violence from the point of view of feminist legal theory and Islamic law. Is sexual consent in accordance with the norms of Indonesian society and a solution to end sexual violence? This study used normative legal research methods. This research uses the research method of the library institute. Statutory approach (statute view) and comparative approach According to this study, sexual consent in the FLT perspective is sexual activity carried out with consent outside the consent of one party, including rape. Freestyle according to Islamic law may only be performed within the bonds of marriage, but outside of the bonds of marriage, such acts constitute adultery, even if done with consent or voluntarily. Not only is it not in accordance with the customs of Indonesian society, but it also contradicts the principles of Pancasila. Because sexual consent focuses only on "effect resolution" rather than "cause prevention," it does not seem to serve as a solution to stop sexual violence.